Appealing to Emotion: The Pension System in the Discourse of Economic Experts in the Chilean Press - Campos Rojas, César; González Arias, Cristian (Íkala, Revista de Lenguaje y Cultura, 2022)
Emotive language is the deliberate strategic use of emotions in discourse. Due to its role in building meaning on public affairs, it is important to explore how it is used in mass media, specifically in opinion-editorial columns, one of the journalism genres where it is most common. Given this, in this qualitative research study, we ask the question: How is emotive language used by economic experts in opinion columns published in two Chilean newspapers in relation to retirement policies? Our corpus was made up of 30 opinion-editorial columns published in the economy section, between 2013 and 2019 in the economy section of two main Chilean newspapers: El Mercurio and La Tercera. The columns referred to 7 events that marked the social and media agenda of the retirement fund debate in Chile. Findings show some deliberate emotional display intended to calm criticism of retirement fund administrators and to arise concern among readers about amendments called for by both the Government and social movements. This suggests that the newspapers, through their op-ed writers, have developed an emotional discourse consistent with the project of social influence that guides their participation in public space.